Experimental investigation of surface buoyant jet interactions with grid obstructions: implications for aquaculture - Grifoll, Manel; Cuthbertson, Alan; Peñas-Torramilans, Raquel; Davies, Peter (Frontiers in Marine Science, 2024)
Freshwater inputs originating from terrestrial streams and gullies that discharge into quiescent, semienclosed coastal regions (such as estuaries, tidal inlets or lagoons), typically provide point sources of nutrients (e.g. nitrates, phosphates) and/or contaminants (e.g. pesticides, pathogens) that may have a deleterious impact on water quality. Many of these sheltered coastal regions also increasingly support aquaculture operations, which can therefore be directly impacted by nutrient and contaminant inputs. Dynamically, these terrestrial freshwater inflows behave as surface buoyant jets or plumes within the coastal saline or brackish receiving waters, due to the salinity-induced density gradients. As such, the presence of infrastructure associated with aquaculture operations in sheltered coastal waters can provide obstruction to the propagation characteristics and residence times for these surface freshwater flows. Consequently, an improved physical understanding of the flow-structure interaction is clearly crucial to assessing the potential contamination risk of aquaculture products. The aim of the current study is therefore to explore, through scaled laboratory experiments within a channel-basin facility, the impact of physical obstruction induced by a vertical grid structure on the flow evolution of a 2D -3D expanding, surface buoyant plume. Two grid obstructions with different solidity ratios are tested, along with surface gravity currents of different density excesses and freshwater inflows to infer the influence of different parametric conditions on the propagation, blockage and mixing characteristics of the surface current in the vicinity of the grid obstruction. Measurements of the velocity structure and thickness of the expanding surface plume are obtained by ultrasonic velocity profilers, while the density excess in the evolving plume is measured by micro-conductivity probes. Dye visualisation results also show that, in the presence of the grid obstruction, the generation of shear-induced billows at the lower interface of the expanding surface current is largely blocked and a local deepening of the fresh-salt water interface in the immediate vicinity of the grid obstruction is observed. In this sense, the obstruction imposed by aquaculture infrastructure in coastal domains can have a considerable influence of the local turbulent mixing and vertical transfer of substances but is likely to have relatively minimal impact in the final dispersion.